A Spheroid Model of Early and Late‐Stage Osteosarcoma Mimicking the Divergent Relationship between Tumor Elimination and Bone Regeneration. Issue 7 (24th October 2021) - Freeman, Fiona E.; Burdis, Ross; Mahon, Olwyn R.; Kelly, Daniel J.; Artzi, Natalie
Abstract: Osteosarcoma is the most diagnosed bone tumor in children. The use of tissue engineering strategies after malignant tumor resection remains a subject of scientific controversy. As a result, there is limited research that focuses on bone regeneration postresection, which is further compromised following chemotherapy. This study aims to develop the first co‐culture spheroid model for osteosarcoma, to understand the divergent relationship between tumor elimination and bone regeneration. By manipulating the ratio of stromal to osteosarcoma cells the modelled cancer state (early/late) is modified, as is evident by the increased tumor growth rates and an upregulation of a panel of well‐established osteosarcoma prognostic genes. Validation of the authors' model is conducted by analyzing its ability to mimic the cytotoxic effects of the FDA‐approved chemotherapeutic Doxorubicin. Next, the model is used to investigate what effect osteogenic supplements have, if any, on tumor growth. When their model is treated with osteogenic supplements, there is a stimulatory effect on the surrounding stromal cells. However, when treated with chemotherapeutics this stimulatory effect is significantly diminished. Together, the results of this study present a novel multicellular model of osteosarcoma and provide a unique platform for screening potential therapeutic options for osteosarcoma before conducting in vivo experiments. Abstract : Osteosarcoma is the most diagnosed bone tumor in children. The effect of tissue engineering strategies following malignant tumor resection on tumor state remains elusive. The authors have developed an osteosarcoma co‐culture spheroid model to mimic early versus late cancer state, providing a unique platform for screening potential therapeutic options and concentrations of drugs for osteosarcoma before conducting in vivo experiments.